2018
DOI: 10.3390/en11040855
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Energy-Related Greenhouse Gas Emission in the Korea’s Building Sector: Use National Energy Statistics

Abstract: Every country in the world is striving to deal with climate change such as global warming and environmental pollution caused by greenhouse gas emission as well as the depletion of fossil fuel including oil, coal, gas, etc. Countries have set long-term greenhouse gas emission reduction targets in this effort. Korea announced its goal to reduce the national greenhouse gas in medium-and long-term by 25.7% of the observed value of 2030 greenhouse gas emission (BAU) in 2011, and set to reduce the greenhouse gas by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The Intergovernmental Panel on Climate Change [5] reported that the global building sector is responsible for approximately 19% of all the GHG emissions. In South Korea, energy consumption in the building sector accounted for approximately 17% of the country's total energy consumption in 2015 and about 20% of all the GHG emissions [6]. As the building sector has been identified as the sector with the greatest potential to reduce GHG emissions in a cost-effective manner [7], innovations in the design of buildings are necessary to cope with climate change and reduce GHG emissions in South Korea as well as on a global scale [8].…”
Section: Background and Purposementioning
confidence: 99%
See 4 more Smart Citations
“…The Intergovernmental Panel on Climate Change [5] reported that the global building sector is responsible for approximately 19% of all the GHG emissions. In South Korea, energy consumption in the building sector accounted for approximately 17% of the country's total energy consumption in 2015 and about 20% of all the GHG emissions [6]. As the building sector has been identified as the sector with the greatest potential to reduce GHG emissions in a cost-effective manner [7], innovations in the design of buildings are necessary to cope with climate change and reduce GHG emissions in South Korea as well as on a global scale [8].…”
Section: Background and Purposementioning
confidence: 99%
“…According to Kim and Jeong [6], as the energy consumption by buildings in South Korea is rapidly increasing and because the building sector has shown outstanding potential in reducing its energy consumption, reducing GHG emissions in the sector should be a key measure of South Korea's national plan to reduce GHG emissions, overall. Although the South Korean government set an energy reduction target of 18.1%, or 35.8 million ton CO 2 eq, in business as usual (BAU) by 2030, it raised the target to 32.7% (64.5 million ton CO 2 eq) in July 2018 [9].…”
Section: Background and Purposementioning
confidence: 99%
See 3 more Smart Citations